Forecast model of airport haze visibility and meteorological factors based on SVR-RBF model. Issue 1 (February 2021) - Liu, Dazheng; Jiang, Tao; Zhang, Yangchun; Wang, Yingjie; Pan, Xiaotian; Wu, Jianping
Abstract: All kinds of meteorological elements near the airport directly affect the dissipation process of fog, which also affects the visibility. The correlation analysis of temperature, humidity, dew point temperature, air pressure, wind speed and other meteorological factors with visibility Runway Visual Range (RVR)and Meteorological Optical Visual Range (MOR)was carried out by SPSS. It was found that the four variables, TEMP, RH, WS2A and PAINS, had great influence. In this paper, the above four variables are selected as inputs to nonlinear fit the RVR value of visibility. Combined with Radial Basis Function (RBF), it is found that SVM-RBF model has better generalization ability and fitting degree.